Multi-Objective Trajectory Optimization for Rigid-Flexible Coupling Spray-Painting Robot Integrated with Coating Process Constraints - Feng Xu; Bin Zi; Jingyuan Wang; Zhaoyi Yu (Chinese Journal of Mechanical Engineering)
Abstract Robot-automated spraying is widely used in various fields, such as the automotive, metalworking, furniture, and aerospace industries. Spraying quality is influenced by multiple factors, including robot speed, acceleration, end-effector trajectory, and spraying process constraints. To achieve high-quality spraying under the influence of multiple factors, this study proposes a multi-objective optimization method for the spraying trajectory that integrates spraying process constraints into the optimization process. First, a 7-degree-of-freedom rigid-flexible coupling serial spray painting robot system is introduced, which includes a motion decoupling mechanism and a tension amplification mechanism. Subsequently, a paint deposition model for the spray gun was established, and the influence of process constraints on spraying quality was analyzed. Trajectory planning for the spray painting robot, based on the septic B-spline interpolation method, was then performed. Based on this foundation, objective functions and constraint equations for spraying trajectory optimization were established. A multi-objective trajectory optimization method for spraying by the robot is proposed based on the NSGA-II, which integrates the spraying process constraints. Finally, a prototype system of a 7-degree-of-freedom rigid-flexible coupling serial spray painting robot was constructed. Simulations and spraying experiments were conducted to verify the effectiveness of the proposed multi-objective trajectory optimization method. This paper presents a multi-objective optimization method for the spraying trajectory of a robot. In the proposed method, the optimized spraying trajectory is generated with the spraying process as the constraint and time, energy consumption, and impact during the spraying operation of the robot as the optimization objectives.